Efektifitas Penggunaan Rel R60 1435mm Pada Pengoperasian Kereta Api Jalur Makassar-Pare Pare - Triatmaja, Firmawan (Program Studi Teknik Sipil Universitas Bosowa, 2024)
The construction of the Makassar – Parepare Railway in South Sulawesi currently uses the R60 rail type and the spur width is 1435mm, currently this type of rail is the first rail type used in Indonesia because the majority in Java and Sumatra still use the R54 rail type and the 1067mm spur width. . For this reason, this research review aims to calculate the effectiveness of the two types of rail based on the cross-carrying capacity of PT Tonasa cement freight transport in the 2050 projection from Tonasa Station - Makassar Newport Station. Things that need to be prepared in this research include collecting primary data and secondary data in the form of an outline map of the Makassar – Parepare railway line construction, the amount of PT Tonasa cement production and calculating production projections in 2050, data on the needs for facilities that are planned to be used in South Sulawesi, calculate the effectiveness of the number of carriages needed and the frequency of train trips between the rail type R60 1435 and the rail type R54 1067. The results of this study obtained a plan for the number of cement transportation from Tonasa Station - Makassar Newport Station of 3,237,590 tons. The transport capacity of the R60 1435mm rail type saves 297 tons/train more than the R54 1067mm rail type, and saves more on the frequency of train trips from 10x trips to 5x train trips.